PROTOTIPE PENGHITUNG TELUR AYAM RAS PADA KANDANG AYAM MENGGUNAKAN ESP8266 DAN SENSOR ULTRASONIC BERBASIS IOT - Hasnita sari; Dedy Hendryadi; Juniarti Iryani (Institut Teknologi dan Bisnis Bina Adinata, 2025)
This study aims to (1) Make an automatic egg counter prototype, (2) Know how the automatic egg counter prototype works, (3) Know the response of laying hen cage owners. This study uses the prototype research method. Prototype research has several stage of research, namely needs analysis, rapid design, build prototype, evaluate initial users, improve prototype, implement and maintain. The results of the study showed that: (1) The prototype of a purebred chicken egg counter in a chicken coop used an esp 8266 and an iot-based ultrasonic sensor was made based on ac curate research results and thoughts and valid data by carrying out various stages of existing research and this prototype was tested on farms owned by Mrs. Darmiati who is in jonjoro, panggaloang village (2) The user’s perception says that this prototype is good, and in accordance with the previously designed system and one day it can be applied directly to the chicken coop so that it can help with egg counting work (3) Based on the data obtained from the results prototype trials on two respondents obtained good results very positive with a percentage value of 81,1% and the results of these calculations will appear in the blynk application.